Is Quantitative Determination of Fibrin(ogen) Degradation Products and Thrombin-Antithrombin III Complexes Useful to Diagnose Deep Venous Thrombosis in Outpatients? - van Bergen, Paul F M M; Knot, Eduard A R; Jonker, Jan J C; de Boer, Auke C; de Maat, Moniek P M (Thrombosis and Haemostasis, 1989)
We studied the diagnostic value of recently introduced ELISA’s for the determination of thrombin-antithrombin III (TAT) complexes, fibrin degradation products (FbDP), fibrinogen degradation products (FgDP) and total degradation products (TDP) for deep venous thrombosis (DVT) in plasma of 239 consecutive outpatients, suspected for DVT by their family doctor. DVT was confirmed by impedance plethysmography in 60 patients. Using the 95th percentile range of 42 healthy volunteers the sensitivity for the detection of DVT was: 37% for TAT, 95% for TDP, 92% for FbDP and 90% for FgDP. Specificity was: 88% for TAT, 16% for TDP, 20% for FbDP and 25% for FgDP.We conclude that these assays are of little value in the diagnosis of DVT in outpatients.
Keywords: Predictive value; Deep venous thrombosis; Impedance plethysmography; Thrombin-antithrombin III; Fibrin(ogen) degradation products